Dynamic Surface Water Management in National Capital Territory of Delhi: The Impact of Geological Formations on Surface Water Management in Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2018)
National Capital Territory of Delhi (NCT Delhi) possesses a region of 1483 sq km. For authoritative purposes, NCT Delhi is separated into 9 areas and 27 tehsils. The typical yearly precipitation of NCT Delhi is 611.8 mm. The precipitation increments from the southwest toward the upper east. About 81 of the yearly precipitation is gotten during the storm months July, August and September. The remainder of the yearly precipitation is gotten as winter downpour and as tempest downpour in the pre and post rainstorm months. NCT Delhi is involved by quartzite between slept with mica schist having a place with Delhi Super Group (Delhi edge) overlain by unconsolidated dregs of Quaternary to Recent age. The thickness of overlying alluvium is profoundly factored on the eastern and western side of the edge. It is commonly thicker (>300m) on the west of the edge. The Quaternary stores as Aeolian and alluvial stores comprise the significant storehouse of groundwater in the zone. Delhi edge goes about as the energize zone for encompassing territories of Delhi.